BK channels mediate a presynaptic form of mGluR-LTD in the neonatal hippocampus - Carlos Ancatén-González; Rodrigo C. Meza; Naileth Gonzalez-Sanabria; Ignacio Segura; Alejandro Alcaino; Antonio Peña-Pichicoi; Ramón Latorre; Chiayu Q. Chiu; Andrés E. Chávez (Proceedings of the National Academy of Sciences, 2025)
BK channels can control neuronal function, but their functional relevance in activity-dependent changes of synaptic function remains elusive. Here, we report that repetitive low-frequency stimulation activates BK channels through 12(S)HPETE, an arachidonic acid metabolite, produced downstream of postsynaptic metabotropic glutamate receptors (mGluRs) to trigger long-term depression (LTD) at CA3–CA1 synapses in hippocampal slices from P7–P10 mice. Activation of BK channels is subunit specific, as paxilline but not iberiotoxin blocked mGluR-LTD. Also, 12(S)HPETE does not change the electrophysiological properties of the BK channel when the BKα subunit is expressed alone but increases the channel open probability when the BKα is coexpressed with the β4-subunit. Our findings reveal an interaction between 12(S)HPETE and BK channels to regulate synaptic strength at central synapses and increase our understanding of the mechanisms underlying mGluR-LTD in the neonatal hippocampus that likely contribute to circuit maturation necessary for learning.